Impact of the ENPP1 mutation on bone mineralization and ectopic calcification: evidence from in vitro and in vivo models - Wu, Wanhong; Liu, Luna; Shi, Yingzhou; Zhang, Yidan; Qiu, Renyuan; Yan, Fang (Frontiers in Endocrinology, 2025)
BackgroundEctonucleotide Pyrophosphatase/Phosphodiesterase 1 (ENPP1) plays a key role in mineralization processes, and mutations in this gene are associated with various severe diseases. Clinical case reports have implicated the ENPP1 Y451C mutation in diffuse idiopathic skeletal hyperostosis patients, but its precise impact on bone mineralization and ectopic calcification remains unclear.MethodsWe used bioinformatics tools and in vitro functional assays to assess the impact of the ENPP1 Y451C mutation on protein structure and enzymatic activity. Furthermore, we generated a knock-in mouse model (Enpp1Y433C) to evaluate microarchitecture or signs of ectopic calcification by Micro-CT.ResultsBioinformatics analysis and in vitro assays showed that the Y451C mutation affects the ENPP1 protein’s structure, reducing enzymatic activity by approximately 50%. We successfully generated the Enpp1Y433C knock-in mouse model. However, no significant differences were observed in body phenotype or biochemical markers in Enpp1Y433C mice at 3, 5, and 10 months, compared to wild-type controls. Similarly, no significant changes were observed in bone microarchitecture or signs of ectopic calcification.ConclusionThe ENPP1 Y451C mutation significantly reduces enzymatic activity in vitro, yet the Enpp1Y433C knock-in mouse model shows no significant abnormalities in mineralization, providing additional evidence for the pathogenicity assessment of ENPP1 Y451C variant. Given that these results are from mouse models, further studies are required to clarify its pathogenicity in humans.